A case report of multisystemic sarcoidosis with extracardiac shunt - Shamsudeen, Faris K. (International Journal of Research in Medical Sciences, 2023)
A 61-year-old female patient, presented with complaints of dry cough and gradually worsening dyspnea of 3 months duration, associated with significant weight loss of >14 kg. At presentation, patient was sick, hypoxemic, and tachypneic and system examination revealed fine basal crepitations on auscultation. CT chest showed random pulmonary nodules with bronchiectatic changes. In view of respiratory distress and elevated d-dimer, CT pulmonary angiogram was done and was normal. A contrast echocardiography study hinted towards a significant right to left extracardiac shunt. There was radiological evidence of chronic liver disease with portal hypertension and numerous poorly defined nodular opacities scattered in hepatic and splenic parenchyma in post contrast images. ANA profile was positive for ribosomal-p protein along with elevated serum ACE levels. An ultrasound guided liver biopsy was ultimately performed and histopathology revealed granulomatous lesion in liver compatible with sarcoidosis.